Japanese Society and Lay Participation in Criminal Justice Social Attitudes, Trust, and Mass Media - Fujita, Masahiro (Springer Nature Singapore : Imprint: Springer, 2018)
XVII, 282 p. 29 illus., 20 illus. in color.